"Are You Saying That We're Racist?": Comparing Normative, Political, and Technical Dimensions of Instructional and Disciplinary Policies. Issue 4 (April 2023) - Daramola, Eupha Jeanne; Allbright, Taylor N.; Marsh, Julie A.
Background: In recent years, school districts have experienced a complex policy environment with myriad reforms aimed at addressing longstanding and historically entrenched disparities in opportunities and outcomes between racially minoritized students and White students. One such reform is standards-based accountability, with its emphasis on documenting and addressing racial disparities in testing outcomes. Recently, educators and lawmakers have sought to address persistent racial disproportionality in disciplinary actions. New behavioral policies may be seen as a response to national attention and outrage regarding the "school-to-prison pipeline, " which indicates that school discipline practices contribute to the over-representation of Black men in the criminal justice system. In recent years, local leaders have been tasked with implementing new disciplinary reforms alongside their ongoing efforts at instructional improvement. Purpose: As districts face an increasingly complex policy environment and constrained resources, researchers must understand how district leaders make sense of and manage the varied policies they are tasked with implementing. This study contributes to the knowledge base on K–12 policy implementation by examining how school district leaders manage multiple policies—particularly when some new practices engage beliefs around racial discrimination or structural racism. We contribute to the gap in the literature by asking: What differences emerged in the early implementation processes of an instructional policy and a discipline policy in the Elmwood school district, and what might explain those differences? Research Design: To answer this question, we employ a comparative, embedded case study design and examine extensive qualitative data from a single school district. Oakes's (1992) framework of technical, normative, and political dimensions of policy change guided the analysis and was applied to rich interview data. Conclusions: Overall, our findings highlight significant differences in how Elmwood leadership implemented the two policies. Our study indicates that though both instructional and disciplinary reforms purport to address racial outcome gaps, district leaders may view discipline in a racialized way that they do not view instructional policy. The perceived racialized nature of discipline policy may significantly influence implementation practices. Ultimately, the data suggests that racialized normative beliefs and values, along with political and technical investments, greatly influence the implementation process and raise larger questions about the role of racism in education reform.